Pengaruh Etos Kerja Islam Terhadap Komitmen Kerja Karyawan Yayasan Pondok Pesantren Hidayatullah Surabaya - Pratama, Novandi Arif; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research was aimed to investigate the effect of Islamic work ethics to the organizational commitment on Yayasan Pondok Pesantren Hidayatullah in Surabaya. This study used questionnaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is the organizational commitment and the independent variable (X) is Islamic work ethics. The research sample were taken by nonprobability sampling with purposive sampling method. The research sample was 58 employees work in Yayasan Pondok Pesantren Hidayatullah Surabaya.Based on the findings, it obtained simple linear regression equation : Y = 5,908+0,452X. The magnitude of the influence of Islamic work ethics to the organizational commitment on Yayasan Pondok Pesantren Hidayatullah Surabaya. According to the final summaries of description data analysis from Islamic work ethic variable, that is have a resolute stand and got no effect (X1.3) has the lowest mean value, Yayasan Pondok Pesantren Hidayatullah be expected to capable of keeping and increasing the human resources, in shaping employees resolute and not easily influenced, so as toimprove the islamic work ethic. For the next research can be done with distinguish the permanent employees and not-permanent employees which later result from the study willbe compared to find out the influence of Islamic work ethic to deeper Organizational Commitment.